The Application of Back Massage to Decrease Pain Lavel in Elderly in Social House of Tresna Werdha Bondowoso - Yuwanto, Mahmud Ady (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-